Analysis of FOXE1 rs3758249, IRF6 rs2235375, MTRR A66G in Non-syndromic Cleft Lip and Palate among Indonesian Deutero-Malay Population - Nasroen, Saskia Lenggogeni; Maskoen, Ani Melani; Rahaju, Asih; Darwis, Rudi Satria; Putri, Maulia; Rachman, Levina Azzahra; Zannah, Putry Nurul (Universitas Islam Bandung, 2024)
Non-syndromic cleft lip and palate (NS-CLP) is one of the most common orofacial malformations, with an incidence of 1 in 700 live births worldwide. This study aimed to determine the risk factor for NS-CLP among the Indonesian Deutero-Malay population by analyzing the FOXE1 rs3758249, IRF6 rs2235375, and MTRR A66G polymorphisms. It is a case-control study, using 50 samples of NS-CLP patients and 50 samples of control (for FOXE1 rs3758249 and MTRR A66G), 30 samples of NS-CLP patients, and 30 samples of control (for IRF6 rs2235375). After DNA was extracted, polymerase chain reaction-restriction fragment length polymorphisms (PCR-RFLPs) were performed by using restriction enzymes of Mscl (FOXE1 rs3758249) and Nde1 (MTRR A66G), and sequencing was performed for IRF6 rs2235375. The study was done in the Molecular Genetic Laboratory, Faculty of Dentistry Universitas Padjadjaran Bandung, from September 2023 to January 2024. The chi-square test was used with the exact Fisher's alternatives. The results showed that in FOXE1 3758249, A allele (mutant) was found more in control (OR=0.744, p>0.05), in MTRR A66G, G allele (mutant) was found more in NS-CLP (OR=1.267, p>0.05) meanwhile in IRF6 rs2235375, G allele (mutant) (OR=1.710, p>0.05) was found more in NS-CLP. This study concluded that FOXE1 rs 3758249, IRF6 rs2235375, and MTRR A66G genes were not the risk factor for NS-CLP in the Indonesian Deutero-Malay population. DOI: https://doi.org/10.29313/gmhc.v12i3.14110